Exogenous subclinical hyperthyroidism during adolescence: Effect on peak bone mass - Preamrudee Poomthavorn (2018)
Background: Chronic subclinical hyperthyroidism induced by suppressive doses of L-thyroxine (L-T4) therapy, so-called exogenous subclinical hyperthyroidism, may cause diminished bone mass in postmenopausal women. The effect of subclinical hyperthyroidism during childhood and adolescence on peak bone mass, however, has not been evaluated. Objective: To determine whether exogenous subclinical hyperthyroidism during adolescence, the period of critical bone mass acquisition, would reduce peak bone mass. Patients and methods: Eighteen female adolescents and young adults with Hashimoto's thyroiditis and euthyroid goiter (aged 22.4 ± 4.4 years) who had been treated with suppressive doses of L-T4, 127.5 ± 23.7 μg/day, during adolescenee (age at onset of subclinical hyperthyroidism, 14.2 ± 1.5 years) for 6.3 ± 3.4 years were enrolled in the study. Twenty-nine healthy female volunteers matched for age, weight, height and body mass index served as the controls. Bone mineral density (BMD) was measured by dual energy X-ray absorptiometry. Results: BMD of the lumbar spine, radius, Ward's triangle and total body were comparable in the two groups. In contrast, BMD of the femoral neck, trochanter and shaft of patients was slightly higher than those of controls. There were no correlations between BMD values and clinical parameters. Conclusion: Exogenous subclinical hyperthyroidism during adolescence has no demonstrable detrimental effect on peak bone mass attainment. © Freund Publishing House Ltd., London.